Dynamics of the Composition of Plasmodium Species Contained within Asymptomatic Malaria Infections in the Central Region of Ghana - Dorcas Bredu; Dickson Donu; Linda Eva Amoah (Journal of Tropical Medicine)
Background. Monitoring changes in the composition of the Plasmodium species circulating within the population over a period can inform appropriate treatment recommendations. This study monitored variations in the prevalence of four common human Plasmodium species carried by children with asymptomatic malaria infections over a two-year period. Methods. Two cross-sectional studies were conducted in November 2017 and December 2019. A total of 210 children aged between 4 and 13 years were recruited in 2017, and 164 similarly aged children were recruited in 2019. Approximately 150 μl of finger-pricked blood was used to prepare thick and thin blood smears as well as spot Whatman® #3 filter paper. Genomic DNA was extracted from the dried blood spots and used in PCR to amplify the 18S rRNA gene from four different human Plasmodium parasites. Results. Parasite prevalence by microscopy and the prevalence of P. falciparum detected by PCR was relatively similar at the two time points (Pearson chi-square = 0.405, p=0.525, and Pearson chi-square = 0.452, p=0.501, respectively). However, the prevalence of PCR detectable P. malariae increased by 8.5-fold, whilst P. ovale increased from 0 to 9% in the children sampled in 2019 relative to the children sampled in 2017. The only parasite species identified by microscopy in this study was P. falciparum, and no P. vivax was identified by either microscopy or PCR in the study population during the study period. Conclusion. There is the need to implement molecular diagnostic tools for malaria parasite surveillance in Ghana. This will enable the identification and treatment of all circulating malaria parasites including P. malariae and P. ovale, whose population is expanding in parts of Ghana including Simiw.